2015
DOI: 10.1186/s12936-015-0752-x
|View full text |Cite
|
Sign up to set email alerts
|

Use of Plasmodium falciparum culture-adapted field isolates for in vitro exflagellation-blocking assay

Abstract: BackgroundA major requirement for malaria elimination is the development of transmission-blocking interventions. In vitro transmission-blocking bioassays currently mostly rely on the use of very few Plasmodium falciparum reference laboratory strains isolated decades ago. To fill a piece of the gap between laboratory experimental models and natural systems, the purpose of this work was to determine if culture-adapted field isolates of P. falciparum are suitable for in vitro transmission-blocking bioassays targe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 16 publications
1
14
0
2
Order By: Relevance
“…Moreover, gametocyte production potential in RKL-9 and JDP-8 appeared to be stable after multiple freeze–thaw cycles. Other studies also reported no loss in gametocyte production upon maintenance of isolates in asexual culture for 18 months [ 22 ] and also after cryopreservation [ 13 , 26 , 27 ]. In vitro gametocyte production potential of parasite is strain specific [ 28 ], exhibited in response to ‘nonspecific’ stress in the form of environmental stimuli [ 22 , 23 , 29 ].…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…Moreover, gametocyte production potential in RKL-9 and JDP-8 appeared to be stable after multiple freeze–thaw cycles. Other studies also reported no loss in gametocyte production upon maintenance of isolates in asexual culture for 18 months [ 22 ] and also after cryopreservation [ 13 , 26 , 27 ]. In vitro gametocyte production potential of parasite is strain specific [ 28 ], exhibited in response to ‘nonspecific’ stress in the form of environmental stimuli [ 22 , 23 , 29 ].…”
Section: Discussionmentioning
confidence: 95%
“…This might be because very few isolates can reproducibly generate gametocytes in high yield in vitro and also show a gradual loss of gametocyte producing potential in continuous culture [ 23 ]. This makes it difficult to study the process of gametocytogenesis [ 23 , 24 ] and to perform gametocytocidal drug screening due to the dependency on cryopreserved stabilates with minimum passage in order to preserve gametocyte production phenotype [ 13 ]. The two field isolates, RKL-9 and JDP-8 used in present study did not show any significant reduction in gametocyte production potential in vitro for at least 6 months in asexual culture.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Exflagellation inhibition assays were performed using published protocols ( Leba et al., 2015 , Bhattacharyya and Kumar, 2001 ). Briefly, 1.5 mL tube containing 170 μL of culture medium (RPMI 1640 medium with 25 mM HEPES, 50 mg/L hypoxanthine, 2 g/L sodium bicarbonate, 10% human serum) was preheated at 37 °C with the dye pre-dissolved in water for a final concentration of 1 μM.…”
Section: Methodsmentioning
confidence: 99%